Postoperative Hormonal and Water Balance Disturbances After Non-Functioning Pituitary Macroadenoma Surgery - Yudha, Nyoman; Setiabudi, Patan; Abellia, Gaby (Universitas Brawijaya, 2024)
Non-functioning pituitary adenomas (NFPAs) are common sellar region tumors. Certain pituitary adenomas are categorized as functional, as they arise from specific cell types that excessively secrete hormones. In contrast, non-functional adenomas do not secrete hormones but can potentially compress the surrounding regions. The lack of hormonal activity in NFPAs often leads to a delayed diagnosis. It becomes clinically significant when the adenoma gets larger and starts causing symptoms. A 52-year-old man presented with visual field impairment since two years ago and throbbing headaches for the last three months. He was found to have pituitary macroadenoma and no hormonal excess was detected. He was diagnosed with non-functioning pituitary macroadenoma, then underwent endonasal endoscopic transsphenoidal hypophysectomy as a surgical procedure in our institute. A surgical procedure to remove pituitary adenomas can lead to high chance of complications in pituitary hormone regulation due to the manipulation of the pituitary gland and its stalk, such as water balance imbalance and hormonal disturbances. Endonasal endoscopic transsphenoidal hypophysectomy as a surgical procedure in treating pituitary macroadenoma has proven effective, resulting in good outcomes. A multidisciplinary approach involving specialists in endocrinology, ophthalmology, and neurosurgery is essential for the comprehensive evaluation of patients with pituitary adenoma.